IDNLearn.com: Where questions are met with accurate and insightful answers. Join our knowledgeable community to find the answers you need for any topic or issue.

Complete the truth table for the inverse of a conditional statement.

| [tex]\( p \)[/tex] | [tex]\( q \)[/tex] | [tex]\( p \rightarrow q \)[/tex] | [tex]\( \sim p \rightarrow \sim q \)[/tex] |
|:---:|:---:|:---:|:---:|
| T | T | T | F |
| T | F | F | [tex]\(\square\)[/tex] |
| F | T | T | [tex]\(\square\)[/tex] |
| F | F | T | [tex]\(\square\)[/tex] |


Sagot :

To solve the truth table values for the inverse of a conditional statement, we need to evaluate each case:

The inverse of [tex]\( p \rightarrow q \)[/tex] is [tex]\( \sim p \rightarrow \sim q \)[/tex].

Consider the given values:
- [tex]\( p \)[/tex] and [tex]\( q \)[/tex] are the basic statements.
- [tex]\( p \rightarrow q \)[/tex] is the conditional statement "if [tex]\( p \)[/tex], then [tex]\( q \)[/tex]".
- [tex]\( \sim p \rightarrow \sim q \)[/tex] is the inverse "if not [tex]\( p \)[/tex], then not [tex]\( q \)[/tex]".

Let's fill in the missing values for each case:

1. For [tex]\( p = T \)[/tex] and [tex]\( q = F \)[/tex]:
- [tex]\( p \rightarrow q \)[/tex] is False because when [tex]\( p \)[/tex] is True and [tex]\( q \)[/tex] is False, the implication [tex]\( p \rightarrow q \)[/tex] fails.
- [tex]\( \sim p \)[/tex] is False (negation of True), and [tex]\( \sim q \)[/tex] is True (negation of False).
- [tex]\( \sim p \rightarrow \sim q \)[/tex] evaluates to True because [tex]\( \sim p \)[/tex] False implies [tex]\( \sim q \)[/tex] True.

2. For [tex]\( p = F \)[/tex] and [tex]\( q = T \)[/tex]:
- [tex]\( p \rightarrow q \)[/tex] is True because when [tex]\( p \)[/tex] is False, the implication [tex]\( p \rightarrow q \)[/tex] is always True.
- [tex]\( \sim p \)[/tex] is True (negation of False), and [tex]\( \sim q \)[/tex] is False (negation of True).
- [tex]\( \sim p \rightarrow \sim q \)[/tex] evaluates to False because [tex]\( \sim p \)[/tex] True does not imply [tex]\( \sim q \)[/tex] False.

3. For [tex]\( p = F \)[/tex] and [tex]\( q = F \)[/tex]:
- [tex]\( p \rightarrow q \)[/tex] is True because when [tex]\( p \)[/tex] is False, the implication [tex]\( p \rightarrow q \)[/tex] is always True.
- [tex]\( \sim p \)[/tex] is True (negation of False), and [tex]\( \sim q \)[/tex] is True (negation of False).
- [tex]\( \sim p \rightarrow \sim q \)[/tex] evaluates to True because [tex]\( \sim p \)[/tex] True implies [tex]\( \sim q \)[/tex] True.

Therefore, the completed truth table is as follows:
\begin{tabular}{|c||c||c|c|}
\hline [tex]$p$[/tex] & [tex]$q$[/tex] & [tex]$p \rightarrow q$[/tex] & [tex]$\sim p \rightarrow \sim q$[/tex] \\
\hline \hline [tex]$T$[/tex] & [tex]$T$[/tex] & [tex]$T$[/tex] & F \\
\hline \hline [tex]$T$[/tex] & [tex]$F$[/tex] & [tex]$F$[/tex] & T \\
\hline \hline [tex]$F$[/tex] & [tex]$T$[/tex] & T & F \\
\hline \hline [tex]$F$[/tex] & [tex]$F$[/tex] & T & T \\
\hline
\end{tabular}